Teletrabalho: a experiência dos servidores técnicoadministrativos do centro de tecnologia (CT) da universidade federal da paraíba (UFPB) durante a pandemia da Covid-19 - Araújo, Jardel Oliveira (2023)
In early 2020, the Sars-Cov-2 virus surprised the world with its high power of contagion and lethality and made people change their routines with a view to reducing the transmissibility. In the field of work, organizations, public and private, for the most part, began to operate through telework, which is the development of work activities at home with the help of information and communication technologies. In the case of public servants, this new reality was much more unknown, since few public organizations went through this experience in previous periods. In this context, the Federal Institutions of Higher Education (IFES) interrupted their face-to-face activities and faced several challenges in the development of their activities. In this way, this work has as main objective understanding the perception of the technical-administrative servers of the Technology Center (CT) of the Federal University of Paraíba (UFPB) in relation to telework during the COVID-19 pandemic. As a collection instrument, an electronic form was applied to the CT servers, which included aspects such as the adequacy of the work environment/tools, task management, communication, impact on physical and mental health and general perception, during the period in which who have been carrying out activities through telecommuting. For the analysis of the data obtained, the degree of agreement of the propositions was used for those arranged in a likert scale and content analysis for the subjective questions. The research showed some points cited in the literature as benefits of telework, such as reduced costs with transportation and reduced travel time, greater family contact, flexible hours, among others, and also some losses such as social isolation, overwork and workload, extra expenses, difficulties in associating work with family, psychological and physical exhaustion, among others. However, in general, the survey showed the preference of public servants for some type of telework regime. As a product of the research, a protocol of suggestions for improving telework in the CT was elaborated based on the difficulties pointed out by the servers.